An experimental study of dense aerosol aggregations - Dhaubhadel, Rajan (Kansas State University, 2008)
We demonstrated that an aerosol can gel. This gelation was then used for a one-step method to produce an ultralow density porous carbon or silica material. This material was named an aerosol gel because it was made via gelation of particles in the aerosol phase. The carbon and silica aerosol gels had high specific surface area (200 – 350 sq m/g for carbon and 300 – 500 sq m/g for silica) and an extremely low density (2.5 – 6.0 mg/cm[superscript3]), properties similar to conventional aerogels. Key aspects to form a gel from an aerosol are large volume fraction, ca. 10[superscript-4] or greater, and small primary particle size, 50 nm or smaller, so that the gel time is fast compared to other characteristic times. Next we report the results of a study of the cluster morphology and kinetics of a dense aggregating aerosol system using the small angle light scattering technique. The soot particles started as individual monomers, ca. 38 nm radius, grew to bigger clusters with time and finally stopped evolving after spanning a network across the whole system volume. This spanning is aerosol gelation. The gelled system showed a hybrid morphology with a lower fractal dimension at length scales of a micron or smaller and a higher fractal dimension at length scales greater than a micron. The study of the kinetics of the aggregating system showed that when the system gelled, the aggregation kernel homogeneity attained a value 0.4 or higher. The magnitude of the aggregation kernel showed an increase with increasing volume fraction. We also used image analysis technique to study the cluster morphology. From the digitized pictures of soot clusters the cluster morphology was determined by two different methods: structure factor and perimeter analysis. We find a hybrid, superaggregate morphology characterized by a fractal dimension of D[subscript f] nearly equal to 1.8 between the monomer size, ca. 50 nm, and 1 micron and D[subscript f] nearly equal to 2.6 at larger length scales up to [similar to] 10 micron. The superaggregate morphology is a consequence of late stage aggregation in a cluster dense regime near a gel point.
Keywords: Aggregation; Gelation; Fractal; Aerosol; Physics, Condensed Matter (0611)